2010
DOI: 10.1209/0295-5075/90/34005
|View full text |Cite
|
Sign up to set email alerts
|

On the origin of intermittency in wave turbulence

Abstract: Abstract. -Using standard signal processing tools, we experimentally report that intermittency of wave turbulence on the surface of a fluid occurs even when two typical large-scale coherent structures (gravity wave breakings and bursts of capillary waves on steep gravity waves) are not taken into account. We also show that intermittency depends on the power injected into the waves. The dependence of the power-law exponent of the gravity-wave spectrum on the forcing amplitude cannot be also ascribed to these co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
33
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 26 publications
(39 reference statements)
9
33
0
Order By: Relevance
“…Implementing an optical filtering technique, we also examine the statistics of intensity of light fluctuations on different scales and we observe that the PDFs show heavy tails that strongly depend on the scales. This reveals an unexpected phenomenon of intermittency that is similar to the one reported in several other wave systems, though they are fundamentally far from being described by an integrable wave equation [30,[32][33][34][35].…”
supporting
confidence: 77%
See 2 more Smart Citations
“…Implementing an optical filtering technique, we also examine the statistics of intensity of light fluctuations on different scales and we observe that the PDFs show heavy tails that strongly depend on the scales. This reveals an unexpected phenomenon of intermittency that is similar to the one reported in several other wave systems, though they are fundamentally far from being described by an integrable wave equation [30,[32][33][34][35].…”
supporting
confidence: 77%
“…We stress here that the deviations from Gaussianity reported in Fig. 3 can be related, in a more general way, to several observations of the intermittency phenomenon previously made in wave turbulence [30,32,33], solar wind [34], or in the Faraday experiment [35]. However, it must be emphasized that all previous works have investigated wave systems that are far from being integrable.…”
supporting
confidence: 72%
See 1 more Smart Citation
“…However, this does not explain the spectrum exponent dependence on the forcing in both cases (see figure 7). It has been shown previously that removing such coherent structures from the wave amplitude signal leads to a gravity spectrum exponent that still depends on the forcing but with less variation, of the order of 25 % (Falcon et al 2010b). Using a similar criterion to define the occurrence of wave breaking events (time intervals where the wave acceleration is greater than six times its standard deviation), we compute the spectrum of the wave signal not including wave breakings.…”
Section: Discussionmentioning
confidence: 99%
“…In the same way, when these wave slope divergences are assumed to be isolated peaks or cusps (D = 0) distributed isotropically and propagating as ω = √ gk, the f −5 Phillips' spectrum is found again. Experimentally, it has been shown that intermittency occurs in gravity wave turbulence (Falcon, Fauve & Laroche 2007a;Nazarenko et al 2010), and is enhanced by coherent structures such as breaking waves (Falcon, Roux & Laroche 2010b). Third, strongly nonlinear waves involved in laboratory experiments may lead to non-local interactions in k-space, dissipation at all scales of the cascade (energy flux not conserved), and no scale separation between linear, nonlinear and dissipating time scales, unlike weak turbulence hypotheses.…”
mentioning
confidence: 99%